SEVERAL MEANINGS IN A SINGLE WORD AS THE SOURCE OF AMBIGUITIES IN A LANGUAGE - Oydin Samadova (Scholar Express Journal, 2023)
Three articles were written about multiple meanings in one word as the source of ambiguities in a language. The semantic structure of a polysemantic word is considered as a system of meanings. Some semantic structures are arranged based on a different principle. In the following list of meanings, one can hardly hope to find a general meaning that covers and holds the rest of the semantic structure of the adjective boring.
Keywords: Language; gestures; system